Mathematics as a science of patterns - Resnik, Michael D. (Clarendon Press ; Oxford University Press, 1997)
Resnik expresses his commitment to a structuralist philosophy of mathematics and links this to a defence of realism about the metaphysics of mathematics - the view that mathematics is about things that really exist.